The Influence Of Location, Word Of Mouth And Halal Label On Purchasing Decisions With Purchase Interest As An Intervening Variable - Sidik Fahmi Mukhamad; Agung Guritno (Universitas Islam Negeri (UIN) Salatiga, 2024)
This research analyzes